2018
DOI: 10.1159/000488743
|View full text |Cite|
|
Sign up to set email alerts
|

Lgr5+CD44+EpCAM+ Strictly Defines Cancer Stem Cells in Human Colorectal Cancer

Abstract: Background/Aims: Although EpCAM+CD44+ cells exhibit more stem-like properties than did EpCAM-CD44- cells, the specificity of EpCAM combined with CD44 in defining CSCs needs further improvement. Lgr5 is used as a biomarker to isolate cancer stem cells (CSCs) in colorectal cancer. However, it remains unclear whether Lgr5, along with EpCAM and CD44, can further identify and define CSCs in colorectal cancer. Methods: Lgr5+CD44+EpCAM+, Lgr5+CD44+EpCAM-, Lgr5+CD44-EpCAM+, Lgr5-CD44+EpCAM+, and Lgr5-CD44-EpCAM-cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 54 publications
1
57
0
Order By: Relevance
“…2,3 Therefore, CSCs have recently gained increasing attention in the field of cancer research. 17 Other studies demonstrated an association of the CSC phenotype with mesenchymal F I G U R E 5 Effect of SB525334 on KLF4 overexpression-induced stemness and tumorigenesis of Lgr5 + CD44 + EpCAM + cells. [32][33][34] Human colorectal CSCs have been well recognized by their specific markers, such as CD133, CD44, CD24, EpCAM, ALDH and Lgr5 together with the CSC malignant profiles, including spheroid and colony formation.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…2,3 Therefore, CSCs have recently gained increasing attention in the field of cancer research. 17 Other studies demonstrated an association of the CSC phenotype with mesenchymal F I G U R E 5 Effect of SB525334 on KLF4 overexpression-induced stemness and tumorigenesis of Lgr5 + CD44 + EpCAM + cells. [32][33][34] Human colorectal CSCs have been well recognized by their specific markers, such as CD133, CD44, CD24, EpCAM, ALDH and Lgr5 together with the CSC malignant profiles, including spheroid and colony formation.…”
Section: Discussionmentioning
confidence: 97%
“…Human Lgr5 + CD44 + EpCAM + cells were sorted and cultured according to our previous study 17 Lentivirus carrying KLF4 cDNA or KLF4 shRNA was purchased from Shanghai GeneChem Co., Ltd. The stably transfected cells were generated according to previous studies 14,18 and then treated with 10 μg/mL puromycin for 48 hours.…”
Section: Lgr5 + Cd44 + Epcam + Cells Culture and Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…year (Ricci-Vitiani et al, 2007). CD44 as a receptor of hyaluronic acid in extracellular matrix (ECM) (Leng et al, 2018), ATP-binding cassette transporter as a drug efflux pump, which promotes tumor cell resistance to chemotherapies (Guo et al, 2018), CD166 as another adhesion molecule to ECM (Shafaei, Sharbatdaran, Kamrani, & Khafri, 2013) are some other robust surface markers of CCSCs (Table 1). Some of these cell surface markers not only are applied in the identification and isolation but also are used in targeted therapy such as in the case of…”
Section: Colon Cancer Stem Cellsmentioning
confidence: 99%
“…Ricci‐Vitiani et al () showed that subcutaneous injection of CD133− colon cancer cells in immunodeficient mice did not have tumor formation ability, whereas CD133+ cells not only reproduced the original tumor but also they could grow as undifferentiated tumorspheres in serum‐free medium for more than 1 year (Ricci‐Vitiani et al, ). CD44 as a receptor of hyaluronic acid in extracellular matrix (ECM) (Leng et al, ), ATP‐binding cassette transporter as a drug efflux pump, which promotes tumor cell resistance to chemotherapies (Guo et al, ), CD166 as another adhesion molecule to ECM (Shafaei, Sharbatdaran, Kamrani, & Khafri, ) are some other robust surface markers of CCSCs (Table ). Some of these cell surface markers not only are applied in the identification and isolation but also are used in targeted therapy such as in the case of LGR5 directed antibody‐drug conjugates.…”
Section: Introductionmentioning
confidence: 99%